2020
DOI: 10.1038/s41416-020-0774-1
|View full text |Cite
|
Sign up to set email alerts
|

Two first-in-human studies of xentuzumab, a humanised insulin-like growth factor (IGF)-neutralising antibody, in patients with advanced solid tumours

Abstract: BACKGROUND: Xentuzumab, an insulin-like growth factor (IGF)-1/IGF-2-neutralising antibody, binds IGF-1 and IGF-2, inhibiting their growth-promoting signalling. Two first-inhuman trials assessed the maximum-tolerated/relevant biological dose (MTD/RBD), safety, pharmacokinetics, pharmacodynamics, and activity of xentuzumab in advanced/metastatic solid cancers. METHODS: These phase 1, open-label trials comprised dose-finding (part I; 3 + 3 design) and expansion cohorts (part II; selected tumours; RBD [weekly dosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 13 publications
5
35
0
Order By: Relevance
“…11 Changes in IGF-axis biomarkers (total IGF-1 and IGF-2, bioactive IGF, and free IGF-1) were consistent with the mechanism of xentuzumab and previous reports. 6 Overall, xentuzumab and afatinib could be safely coadministered, although the combination did not reveal substantial clinical activity in patients with EGFRmþ T790M-negative NSCLC after progression on afatinib. We suggest that such "reversal of resistance" trials represent a novel concept to avoid larger randomized trials for signal detection of rare resistance mechanisms, such as IGF-axis dependency.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…11 Changes in IGF-axis biomarkers (total IGF-1 and IGF-2, bioactive IGF, and free IGF-1) were consistent with the mechanism of xentuzumab and previous reports. 6 Overall, xentuzumab and afatinib could be safely coadministered, although the combination did not reveal substantial clinical activity in patients with EGFRmþ T790M-negative NSCLC after progression on afatinib. We suggest that such "reversal of resistance" trials represent a novel concept to avoid larger randomized trials for signal detection of rare resistance mechanisms, such as IGF-axis dependency.…”
Section: Discussionmentioning
confidence: 95%
“… 11 Changes in IGF-axis biomarkers (total IGF-1 and IGF-2, bioactive IGF, and free IGF-1) were consistent with the mechanism of xentuzumab and previous reports. 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xentuzumab has a binding affinity for both IGF-1 and IGF-2. The advantage of this drug is that it does not target the isoform B of the IR which is involved in glucose metabolism and therefore does not induce the hyperglycaemia and metabolic toxicity observed with IGF-1R targeted therapies or TKIs ( de Bono et al, 2020 ). Xentuzumab has already been evaluated in combination with enzalutamide for the treatment of castration resistant prostate cancer (NCT02204072), however it failed to improve progression free survival over enzalutamide alone.…”
Section: The Gh/igf-1 System and Cancer Riskmentioning
confidence: 99%
“…Similarly, in prostate cancer, xentuzumab + enzalutamide inhibited the growth of castration-resistant patient-derived xenograft (PDX)-derived cells with acquired resistance to enzalutamide and improved in vivo survival [130]. In the clinic, two preliminary studies testing xentuzumab as single agent in advanced solid tumors indicated a good tolerability and preliminary anti-tumor activity [131]. However, a phase Ib/II study indicated that the addition of xentuzumab to everolimus/exemestane did not improve progression free survival in breast cancer patients, leading to early termination of this trial [132].…”
Section: Igfs Neutralizing Antibodies and Ligands Trapmentioning
confidence: 99%